Modified Function Projective Synchronization of Fractional Order Chaotic Systems with Different Dimensions - Hong-Juan Liu; Zhi-Liang Zhu; Hai Yu; Qian Zhu (Discrete Dynamics in Nature and Society)
The modified function projective synchronization of different dimensional fractional-order chaotic systems with known or unknown parameters is investigated in this paper. Based on the stability theorem of linear fractional-order systems, the adaptive controllers with corresponding parameter update laws for achieving the synchronization are given. The fractional-order chaotic system and hyperchaotic system are applied to achieve synchronization in both reduced order and increased order. The corresponding numerical results coincide with theoretical analysis.